Extended bounds of beatty sequence associated with primes - Deraman, Fatanah; Sapar, Siti Hasana; Mohamat Johari, Mohamat Aidil; Mohd Atan, K. A.; Rasedee, A. F. N. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper discusses on the estimation of character sums with respect to non-homogeneous Beatty sequences, over prime where , and is irrational. In particular, the bounds is found by extending several properties of character sums associated with composite moduli over prime. As a result, the bound of is deduced.